Global Fixed-Time Target Enclosing Tracking Control for an Unmanned Surface Vehicle Under Unknown Velocity States and Actuator Saturation - Xinjie Han; Guanglu Ma; Yunsheng Fan; Dongdong Mu; Feng Sun; Linlong Shi; Hongbiao Li (Journal of Marine Science and Engineering, 2025)
This paper presents a global fixed-time control framework to address the target circumnavigation tracking problem of underactuated unmanned surface vehicles (USV) under unknown velocity states, lumped uncertainties, and actuator saturation. At the core of this approach is a novel fixed-time target-enclosing line-of-sight (FTTELOS) guidance law, designed to generate the desired heading angle and surge velocity. To estimate unknown velocities, external disturbances, and unmeasured system states, a set of fixed-time observers is constructed, consisting of a velocity observer, a disturbance observer, and a high-dimensional extended state observer (HFTESO). Moreover, to enhance robustness and effectively tackle actuator saturation, the control scheme incorporates a fixed-time sliding mode controller, a dynamic auxiliary system, and a fixed-threshold event-triggered mechanism. Simulation results using SimuNPS demonstrate that the proposed method enables rapid and smooth target circumnavigation, with all system errors converging to an arbitrarily small neighborhood of the origin within a fixed time. Theoretical analysis and simulation studies confirm the effectiveness and robustness of both the FTTELOS guidance law and the integrated control strategy. Quantitatively, compared with the traditional target-enclosing line-of-sight (TELOS) method, the proposed FTTELOS reduces the convergence time of the distance error δe from 13.64 s to 10.22 s and the angular error ϕe from 10.46 s to 7.52 s, demonstrating a significant improvement in convergence speed and overall control performance.

Modeling the reachable set of ships in the presence of realistic wave disturbances - Dongdong Mu; Xiaomeng He; Mingyang Yin; Hongbiao Li; Linlong Shi; Yunsheng Fan; Xiaojie Sun (Ocean Engineering, 2025)

Superhydrophobic graphene nanowalls for electromagnetic interference shielding and infrared photodetection via a two-step transfer method - Qi Yang; Jun Yang; Linlong Tang; Heng Zhang; Dapeng Wei; Haofei Shi; Xingzhan Wei; Yupeng Zhang; Bin Su (Chemical Engineering Journal, 2023)

Predicting longitudinal tunnel deformation due to deep excavation-induced ground movement - Linlong Mu; Peiyun Zhang; Zhenhao Shi; Mengxi Zhu; Zhiwang Gu (Tunnelling and Underground Space Technology, 2023)

Coupled CFD–DEM Investigation of Erosion Accompanied by Clogging Mechanism under Different Hydraulic Gradients - Linlong Mu; Peiyun Zhang; Zhenhao Shi; Maosong Huang (Computers and Geotechnics, 2023)